Characterization of gaseous and particulate emissions from combustion of algae based methyl ester biodiesel - Fisher, Bethany, author; Marchese, Anthony John, 1967-, advisor; Olsen, Daniel B., committee member; Volckens, John, committee member (Colorado State University. Libraries, 2009)
The advantages to using biodiesel in place of petroleum diesel are also accompanied by disadvantages. Biodiesel is usually made from crops that are also used to produce food. The land and water use impacts would be profound if current biodiesel feedstocks were used to displace a significant portion of current global petroleum diesel consumption. Oil-producing algae is a favorable alternative to the more common biodiesel feedstocks (soy, canola, etc.) because it does not compete with food sources, does not require arable land to grow and has the potential to produce significantly more oil per area per year than any other oil crops. However, the fatty acid composition of the oil produced by algal species currently under consideration for fuel production differs from that of the more common vegetable oils in that it often includes high quantities of long chain and highly unsaturated fatty acids. When transesterified into fatty acid methyl esters (FAME) biodiesel, the unique fatty acid composition could have a substantial impact on emissions such as Nitrogen Oxides (NOx) and particulate matter (PM). Accordingly, the goal of this study was to examine the effect of the chemical structure of algal methyl esters on pollutant emissions from a diesel engine operating on algae-based FAME biodiesel. Tests were performed on a 2.4 L, 39 kW John Deere 4024T, off-road diesel engine meeting USEPA Tier 2 emissions regulations. The engine was fitted with a unique, low-volume fuel system that enabled emissions tests to be conducted with small specialty fuel samples. Tests were performed on 9 different fuel blends at 2 different engine loading conditions. Exhaust gas measurements were made using a 5-gas emissions analysis system that includes chemiluminescence measurement of NOx, flame ionization detection of total hydrocarbons, paramagnetic detection of oxygen and non-dispersive infrared detection of CO and CO2. Particulate matter was characterized using an Aerosol Mass Spectrometer (AMS), which is capable of direct measurement of particle composition. The PM size distributions (between 10 to 1000 nm) were measured using a Sequential Mobility Particle Sizer. Total PM mass emissions were measured using gravimetric analysis of Teflon filters and the ratio of elemental carbon to organic was measured using thermo-optical analysis of quartz filters. Experiments were performed with ultra-low sulfur diesel, soy biodiesel (both pure biodiesel, B100, and a blend of 20% biodiesel and 80% diesel, B20), canola biodiesel (B20 and B100), and two synthetic algal methyl ester formulations (B20 and B100 for each). Combustion of algal methyl esters resulted in decreased NOx relative to both canola and soy biodiesel and ULSD, in contrast to previous research that examined the effect of fatty acid saturation and chain length on NOx emissions. A correlation was found between NOx emissions and premixed burn fraction, which provides an explanation for these results. Emissions of formaldehyde and organic PM were found to be slightly elevated with the two algal fuels in comparison with the traditional feedstocks. Particle size distribution, total PM mass, total hydrocarbons, CO and acetaldehyde emissions were similar between the different types of biodiesel.
Department Head: Allan Thomson Kirkpatrick.